Pengaruh Upah, Motivasi Kerja, dan Kepuasan Kerja terhadap Kinerja Pekerja pada Industri Manufaktur di Kota Makassar - Umar, Akmal (Universitas Brawijaya, Indonesia, 2012)
The purpose of this study is to analyze and assess (1) the influence wages to the employee's workmotivation; (2) the influence wages to the employee's job satisfaction; (3) the influence work motivation tothe employee's performance; (4) the influence job satisfaction to the employee's performance; (5) the influencewages to the employee's performance; (6) the influence job satisfaction to the employee's work motivationin manufacturing industry in Makassar Industrial Area. The populations in this study are all operationalemployees (executive level) of 20 manufacturing industries in Makassar Industrial Area. The samplewas taken from 300 workers by random sampling. The model data analysis in this study used SEM (StructuralEquation Modeling). The result of this study indicates that wages, work motivation, and employee'sjob satisfaction significantly influenced by the employee's performance at manufacturing industries inMakassar Industrial Area. It also indicates that job satisfaction affects employee's work motivation, positively.